Utilization of Flutter Framework in Developing an Android-Based Cooking Recipe Application - Algadrie, Saniah Evatri; Sela, Enny Itje (Kirana Publisher (KNPub), 2024)
Cooking has become a common activity in everyday life. Cooking activities require recipes that are used as a guide in processing food ingredients into a dish. The collection of recipes in print media has not been able to meet the needs of users with a dynamic lifestyle. Therefore, researchers developed an android mobile-based cooking recipe application which is a solution to make it easier for users to find and practice recipes efficiently. This research uses a design process using the System Development Life Cycle (SDLC) approach. And in making this application, researchers used the Flutter framework with the Dart programming language which is designed for fast, efficient, and high-performance application development. Later this application will relate to the API (Application Programming Interface) of TheMealDB which provides recipe data. The result of this research is an application that is able to display innovative cooking recipes so that users can easily find and implement cooking recipes and support the improvement of cooking skills and creativity.